Implementation of public administration strategies in library management to enhance reading interest and literacy culture: A study at the library and archives office of Lamandau regency - Nova, Jerry; Saleh, Choirul; Hermawan, Hermawan; Hanafi, Imam (Edelweiss Applied Science and Technology, 2025)
A strong literacy culture is a key indicator in determining the quality of a nation’s human resources. However, Indonesia continues to face significant challenges in fostering reading interest, particularly at the regional level. This study aims to analyze the strategies implemented by the Library and Archives Office of Lamandau Regency to enhance reading interest and cultivate a literacy culture. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis, which were then examined using thematic analysis techniques. The findings reveal that literacy development strategies in Lamandau Regency encompass strengthening library access, innovating digital literacy services, and enhancing librarian capacity. Mobile library programs, the provision of more diverse reading materials, and collaborations with schools and literacy communities serve as key initiatives in fostering public reading interest. However, this study also identifies several challenges in implementing these strategies, including budget constraints, limited utilization of technology in library services, and a shortage of competent librarians. These findings indicate that the success of literacy culture development is not solely dependent on the availability of reading materials but also on the effectiveness of literacy policies integrated with regional development strategies. Therefore, this study recommends a more adaptive, community-based strategy model supported by sustainable policies to overcome barriers in literacy implementation at the regional level. This study contributes to the development of public administration theories in the literacy context and offers practical insights for policymakers to enhance the effectiveness of library strategies in fostering an inclusive and sustainable literacy culture.